Provision and experience of care among women with hypertension in pregnancy: a multi-center qualitative study in Ghana - Adu-Bonsaffoh, Kwame; Tamma, Evelyn; Nwameme, Adanna; Dako-Gyeke, Phyllis; Srofenyoh, Emmanuel; Ansah, Evelyn K; Grobbee, Diederick E; Franx, Arie; Browne, Joyce L (BioMed Central Ltd., 2023)
BACKGROUND: Hypertensive disorders of pregnancy (HDP) remain a leading global health problem with complex clinical presentations and potentially grim birth outcomes for both mother and fetus. Improvement in the quality of maternal care provision and positive women's experiences are indispensable measures to reduce maternal and perinatal adverse outcomes. OBJECTIVE: To explore the perspectives and lived experiences of healthcare provision among women with HDP and the associated challenges. METHODS: A multi-center qualitative study using in-depth interviews (IDIs) and focus group discussions (FGDs) was conducted in five major referral hospitals in the Greater Accra Region of Ghana between June 2018 and March 2019. Women between 26 and 34 weeks' gestation with confirmed HDP who received maternity care services were eligible to participate. Thematic content analysis was performed using the inductive analytic framework approach. RESULTS: Fifty IDIs and three FGDs (with 22 participants) were conducted. Most women were between 20 and 30 years, Akans (ethnicity), married/cohabiting, self-employed and secondary school graduates. Women reported mixed (positive and negative) experiences of maternal care. Positive experiences reported include receiving optimal quality of care, satisfaction with care and good counselling and reassurance from the health professionals. Negative experiences of care comprised ineffective provider-client communication, inappropriate attitudes by the health professionals and disrespectful treatment including verbal and physical abuse. Major health system factors influencing women's experiences of care included lack of logistics, substandard professionalism, inefficient national health insurance system and unexplained delays at health facilities. Patient-related factors that influenced provision of care enumerated were financial limitations, chronic psychosocial stress and inadequate awareness about HDP. CONCLUSION: Women with HDP reported both positive and negative experiences of care stemming from the healthcare system, health providers and individual factors. Given the importance of positive women's experiences and respectful maternal care, dedicated multidisciplinary women-centered care is recommended to optimize the care for pregnant women with HDP.
Keywords: Experience of care; Hypertension in pregnancy; Maternal hypertension; Quality of care; Obstetrics and Gynaecology; Reproductive Medicine